Elementary School Students’ Vocabulary Enhancement through YouTube Video-Based Learning - Maryam Sorohiti; Anisa Rahma Hidayah; Sri Rejeki Murtiningsih (Journal of English Language Studies, 2024)
The research objectives are: (1) to investigate the students' vocabulary mastery before using YouTube Video-based learning method, (2) to find out the students' vocabulary mastery after using YouTube Video-based learning method, (3) to perceive the difference in the students' mastery before and after using YouTube Video-based learning method. This research was conducted in a private Islamic elementary school in Yogyakarta for fourth-grade students. The method used in this research is quantitative, which uses a test. A pre-test was given to measure the students’ current vocabulary abilities, with results showing M = 6.00 and SD = 0.88415. Then, a treatment was applied using YouTube video-based media to help students with their vocabulary. To measure the aftereffect, the researcher uses a post-test. The post-test showed that M = 8.68. The results of this study indicated that there is an improvement in using YouTube video-based media for vocabulary learning, and it positively impacted the student's vocabulary enhancement. The study implies that elementary school teachers should use YouTube videos when teaching vocabulary and that elementary schools support the efforts, such as good wi-fi connection, projectors, and room speakers.